Analisis Potensi Pengembangan Pembangkit Listrik Tenaga Mikrohidro di Kota Lhokseumawe: Studi Pustaka - Raazi; M. Saydi Kamarullah (Jurnal Pendidikan Teknik Elektro Undiksha, 2026)
This study aims to examine the potential development of micro-hydro power plants (PLTMH) in Lhokseumawe City through a literature review approach. By collecting and analyzing relevant literature related to water resources, renewable energy, and PLTMH development in Aceh and surrounding areas, the results indicate that the water resources in this region possess significant potential, although further detailed identification is necessary for optimal utilization. Key technical factors such as water flow rate, head, and turbine selection are crucial for successful implementation. The development of PLTMH is expected to improve community energy access, reduce dependence on fossil fuels, and support a sustainable energy transition. With appropriate policy support and community participation, this potential can be realized as a reliable and environmentally friendly energy source.